Al-‘Asher School: The Philosophical of K.H. Ahmad Dahlan’s Character Education - Azaki Khoirudin; Ari Anshori (Universitas Muhammadiyah Surakarta, 2018)
This article is a philosophical reflection of KH. Ahmad Dahlan educational practice. Based on the historical fact that KH. Ahmad Dahlan undertook the character education contained in Surah Al-'Ashr to his students for 7-9 months. This educational practice is manifested in the form of “Pengajian Wal-'Ashri” for young women and “Wal-'Ashri Cadre School” for male youth. This makes the spirit and ethos of al-'Ashr embedded in young men and women, thus creating a